The Relative Importance of Political and Economic Variables in Creditworthiness Ratings. (IMF Working Papers; Working Paper ;, 1998)
This study examines the relative importance of political and economic variables in the determination of a country's standing in credit ratings provided by commercial rating agencies. It finds that creditworthiness appears to be determined primarily by economic variables. While including political events can improve the explanatory power of the regressions, the exclusion of political variables does not bias the parameter estimates for the effects of economic variables.